Gut–lung axis in allergic rhinitis: microbial dysbiosis and therapeutic strategies - Yang, WeiKeng; Wu, Hui; Li, Xiuyun; Wan, Zhi; Kong, Wei; Huang, Congfu (Frontiers in Microbiology, 2025)
BackgroundAllergic rhinitis (AR) affects an estimated 10%–30% of people worldwide and places a significant burden on both health and healthcare systems. Recent research suggests that imbalances in the gut microbiota may contribute to the development of AR by disrupting immune regulation along the gut–lung axis. However, these insights have yet to be fully translated into clinical practice.MethodsWe performed a systematic review of studies published between 2010 and 2025, including clinical research, animal experiments, and multi-omics analyses, retrieved from PubMed, Web of Science, Embase, Cochrane, CNKI, and Wanfang databases. The review aimed to evaluate immune mechanisms mediated by the gut microbiota and assess microbiota-targeted interventions in AR.ResultsPatients with AR consistently show reduced fecal butyrate levels, with several studies reporting significant declines, alongside elevated serum IgE concentrations. These changes are closely linked to gut dysbiosis, characterized by reduced abundance of Faecalibacterium and imbalances in the Bacteroidetes/Firmicutes ratio. Dysbiosis appears to drive activation of the aryl hydrocarbon receptor (AhR) pathway, evidenced by a 1.5-fold increase in the kynurenine/tryptophan ratio (p < 0.05), and contributes to impaired regulatory T-cell function. Experimental evidence supports these associations: in murine models, fecal microbiota transplantation (FMT) reduced nasal IL-13 levels by as much as 60% in one study. In human trials, probiotic supplementation, particularly with Clostridium butyricum, was linked to reductions in serum IgE in some cohorts. Integration of multi-omics datasets further reveals conserved mechanisms, including butyrate-mediated histone deacetylase inhibition and vagus nerve–dependent suppression of mast cell activity. Moreover, combinatorial approaches, such as combining probiotics with FXR agonists, have yielded significant improvements in preclinical models, notably reducing nasal symptom scores.ConclusionGut dysbiosis contributes to the development of AR by disrupting immune–metabolic pathways along the gut–lung axis. Microbiota-targeted interventions hold promise for both the prevention and management of AR, especially in pediatric populations. To achieve long-term impact, public health strategies that combine dietary modifications with measures to reduce air pollution are urgently needed.